TEACHERS AND STUDENTS PERCEPTION TOWARDS ONLINE LEARNING IN ENGLISH LEARNING CLASS 10 MIA SMA MANIAMAS NGABANG IN THE ACADEMIC YEAR OF 2021/2022 - Yumita, Yumita; Selong, Yustina; Tuminah, Tuminah (English Language Education Study Program, 2022)
This study aims to determine the perception of teachers and students towards online learning in class 10 Mia SMA Maniamas Ngabang. The writers were using descriptive qualitative as a method in this research. The subjects were 2 English teachers and 35 students in the academic year of 2021/2022. Data sources in this research were: source (informants), place, and document. The data collection techniques used were questionnaire and interview, while data analysis techniques were data reduction, data presentation, and drawing conclusion. The results of this research were: (1) The learning process was less than optimal, teachers got difficulty in assessing students attitudes, lack of learning media facilities, and unstable internet networks. (2) From the number of 10th grade students at SMA Maniamas Ngabang showed that 11 students were not active in participating the learning process, while 24 students were active in participating the learning. Students were unable to understand learning materials and assignments due to limited space and time, unstable internet network, limited internet quota, and there were some students who did not have android phone. (3) Online learning could make students more independent in learning, but sometime they could not learn without direct role from their teacher.